Coupling and Regulation of Porous Carriers Using Plasma and Amination to Improve the Catalytic Performance of Glucose Oxidase and Catalase - Liao, Lingtong; Meng, Yuling; Wang, Ruiming; Jia, Baolei; Li, Piwu (Frontiers in Bioengineering and Biotechnology, 2019)
Multiple enzyme systems are being increasingly used for their high-efficiency and co-immobilization is a key technology to lower the cost and improve the stability of enzymes. In this study, poly glycidyl methacrylate (PGMA) spheres were synthesized using suspension polymerization, and were used as a support to co-immobilize glucose oxidase (GOx) and catalase (CAT). Surface modification was carried out via a combination of plasma and amination to promote the properties of the catalyzer. The co-immobilized enzymes showed a more extensive range of optimum pH and temperature from 5.5 to 7.5 and 25 to 40°C, respectively, compared to free enzymes. Furthermore, the maximum activity and protein adsorption quantity of the co-immobilized enzymes reached 25.98 U/g and 6.07 mg/g, respectively. The enzymatic activity of the co-immobilized enzymes was maintained at ~70% after storage for 5 days and at 82% after three consecutive cycles, indicating that the immobilized material could be applied industrially.